PENELITIAN TINDAKAN KELAS MODEL GROUP TO GROUP EXCHANGE - Tanti Rahmawati; Fitri Nurlaili (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2019)
This research aims to know the application of cooperative learning model of type group to group exchange on subjects of financial accounting as well as knowing the results of learning students after teaching and learning activities using the learning model Group to group exchange.This research used classroom action research with two cycles and each cycles consist of four steps : planning, action, observing and reflection. The results of this research show that the model of the learning group to group exchange can improve student learning activities. The results of the observation activities of students in cycle 1 of 70% and cycle 2 of 90%. In addition, the results of this research also shows that the model of the learning group to group exchange can also improve student learning outcomes. In cycle 1, of 31 students in attendance who managed to reach the KKM of 61.29%, with average result 80,74 while on cycle 2 of 33 students in attendance who managed to reach the KKM of 89,19%.with average result 84,61.